Fatty Acid Characterization from Flowers of Tulipa Systola Stapf. Using Gas Chromatography-Mass Spectrometry (GC-MS) - Ibrahim, Mohammed F.; Hussain, Faiq H. S.; Zanoni, Giuseppe (Science Journal of University of Zakho, 2016)
The structural analysis of fatty acid mixtures by gas chromatography-mass spectrometry (GC-MS) has been characterized from Tulipa systola Stapf. Flowers, wild plant growing in Kurdistan region-Iraq. The fatty acids of the lipid fraction were mainly saturated fatty acids, the highest value recorded for isopropyl palmitic acid methyl ester (47.02%), glycerol α-palmitic acid methyl ester (19.66%) and stearic acid methyl ester (8.64%). In addition, two unsaturated fatty acids that characterized were oleic acid methyl ester (6.95%) and undecylenic acid methyl ester (2.22%).
Keywords: Tulipa systola; Fatty acid methyl ester; Gas chromatography-mass spectrometry